Pengaruh Pembelajaran Taman Pendidikan Al-Quran terhadap Pencapaian Kompetensi Baca Tulis Al-Quran - Wijayanti, Novi; Astuti, Efi Tri (Edu Berkah Khatulistiwa, 2024)
Al-Quran education is the main thing that must be given to Muslim children, whereas the Al-Quran is the holy book of Muslims. Al-Quran education starts from learning to read and write the Al-Quran, where this learning takes place at school and also outside school hours, namely at the nearest TPQ. This has a huge impact on the development and knowledge of students at school. Al-Quran education at TPQ is more focused and has clearer targets and objectives. This research is field research that uses quantitative methods. The data collection technique involves distributing questionnaires to respondents at SDN 02 Dadapan which is the primary data in this research. The analysis used is simple regression to determine the significance of the influence of variable X on variable Y, and also to determine the magnitude of the influence. The results of this research show that there is a significant influence between TPQ learning on the achievement of Al-Quran reading and writing competency with the results of Tcount > Ttable (3.699 > 2.048) with an influence percentage of 32.8%. With this, TPQ provides benefits to SDN 02 Dadapan, especially in learning to read and write the Al-Quran.